Carbon Dot‐Based Biosensors. Issue 6 (31st March 2021) - Jiang, Wei; Zhao, Yuan; Zhu, Xuecheng; Liu, Huilin; Sun, Baoguo
Abstract : 0D fluorescent carbon dots (CDs), consisting of sp 2 / sp 3 carbon skeletons with functional groups, have the advantages of good chemical stability, high biocompatibility, excellent dispersibility in water, and low photobleaching, as well as low toxicity and low cost. These interesting features allow CDs to be applicable in the field of biological imaging, optoelectronic, and energy devices, especially in the application of biosensors, which are rapidly gaining attention. Herein, CD synthesis methods are summarized in detail, and the basic scientific issues of top‐down and bottom‐up approaches to CDs photoluminescence mechanisms are comprehensively discussed and analyzed. Then, valuable insights into the current status of CD research for biosensor applications are provided and the basic photoluminescence properties of CDs, focusing on the CD photoluminescence mechanism from the aspects of optical absorption, up‐conversion glow, static and dynamic quenching, fluorescence resonance energy transfer (FRET) quenching, photoinduced electron transfer (PET) quenching, and inner filter effect (IFE) quenching, are explained. Finally, a brief outlook is given to stimulate new ideas and promote further research on the potential use of CDs in various biosensor fields. Abstract : Herein, valuable insights into the current status of carbon dot (CD) research for biosensor applications are provided and the basic photoluminescence properties of CDs are explained, focusing on the CD photoluminescence mechanism from the aspects of optical absorption, up‐conversion glow, static and dynamic quenching, fluorescence resonance energy transfer quenching, photoinduced electron transfer quenching, and inner filter effect quenching.